Analisis Minat Berwirausaha Pada Mahasiswa - Gumilar, Raditya Cakra; Wolor, Christian Wiradendi; Marsofyati, Marsofyati (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2024)
Entrepreneurship is closely related to concepts and practices related to the establishment, management, and development of a business or business with the aim of creating economic value. It involves several activities, including ideas, business planning, resource acquisition, operations management, marketing, innovation, risk-taking, and so on. The purpose of this study is to determine the interest in entrepreneurship in students of the faculty of economics which includes the development of student entrepreneurial interest and the obstacles experienced in developing entrepreneurial interest. This research uses a descriptive qualitative approach, namely by describing and analysing the problems found. Sampling using Purposive Sampling method. The primary data in this study was obtained by making observations, interviews, and documentation on students of the faculty of economics in 2020-2022. From the results of this study, economics’ faculty students are less interested in entrepreneurship. The lack of entrepreneurial practice in lectures and fixating on theory is the main reason students are less interested in entrepreneurship itself. Organizing competitions such as pitch deck competitions for students to encourage student interest and competition spirit in the field of entrepreneurship. Abstrak Kewirausahaan erat kaitannya dengan konsep dan praktik yang berkaitan dengan pendirian, pengelolaan, dan pengembangan suatu usaha atau bisnis dengan tujuan menciptakan nilai ekonomi. Ini melibatkan beberapa kegiatan, termasuk ide, perencanaan bisnis, akuisisi sumber daya, manajemen operasi, pemasaran, inovasi, pengambilan risiko, dan sebagainya. Tujuan penelitian ini adalah untuk mengetahui minat kewirausahaan pada mahasiswa fakultas ekonomi yang meliputi pengembangan minat kewirausahaan mahasiswa dan hambatan yang dialami dalam mengembangkan minat kewirausahaan. Penelitian ini menggunakan pendekatan kualitatif deskriptif, yaitu dengan mendeskripsikan dan menganalisis permasalahan yang ditemukan. Pengambilan sampel menggunakan metode Purposive Sampling. Data primer dalam penelitian ini diperoleh dengan melakukan observasi, wawancara, dan dokumentasi terhadap mahasiswa fakultas ekonomi tahun 2020-2022. Dari hasil penelitian ini, mahasiswa fakultas ekonomi kurang tertarik untuk berwirausaha. Minimnya praktik kewirausahaan dalam perkuli-ahan dan terpaku pada teori menjadi alasan utama mahasiswa kurang tertarik dengan kewirausahaan itu sendiri. Menyelenggarakan kompetisi seperti lomba pitch deck bagi maha-siswa untuk mendorong minat mahasiswa dan semangat kompetisi dalam bidang kewirausahaan.